STUDI LITERATUR TENTANG : TEKNIK BUTEYKO DAN TEKNIK LATIHAN PERNAPASAN DIAFRAGMA TERHADAP PUNCAK LAJU ALIRAN PERNAPASAN PASIEN ASMA - Nurul Hidayah; Rahmi Syarifatun Abidah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Asthma is a disease that is often found in the community, based on data from the World Health Organization in 2018, as many as 300 million asthma sufferers and 225 thousand sufferers died of asthma worldwide. Buteyko technique and diaphragmatic breathing exercise technique can be one of the non-pharmacological adjunct therapies to reduce asthma symptoms also can increase peak expiratory flow. Besides, both of these techniques are still rare people who know that the buteyko technique and diaphragmatic breating exercise can reduce the frequency of asthma symptoms. The purpose of this literature review study is to determine the effectiveness of the Buteyko technique and diaphragmatic breathing exercise on peak expiratory flow rates in asthma patients. In this literature study Journal searches were traced nationally and internationally through Google Schoolar, Pubmed, and DOAJ published from 2010-2020 using selected keywords namely: ((((asthma) AND buteyko) AND diaphragmatic breating exercise) OR breathing exercise) OR muscle training. Based on the literature search results through publication in the database and using keywords that have been adapted to MeSH, researchers get 21 articles that match these keywords. An assessment based on the eligibility of the inclusion and exclusion criteria was found as many as 10 articles that could be used in the literature review. Based on the analysis and synthesis of the article, it can be concluded that the effectiveness of the Buteyko technique and diaphragmatic breathing exercise on peak expiratory flow rates it can be concluded that there is no significant difference between the two interventions in increasing peak expiratory flow rate.